2009
DOI: 10.1097/jto.0b013e31819d18f9
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tracheal Tumors: Review of 37 Cases

Abstract: Papillomas were difficult to manage, however, other benign tumors were successfully treated. Among malignant tumors, surgery should be considered as the first choice of treatment, regardless of the histologic type, if the tumors are resectable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 16 publications
(23 reference statements)
2
37
0
9
Order By: Relevance
“…Many studies in different parts of the world have shown that resection extends the survival of patients with ACC [3,5,8,9,[13][14][15][16][17]. In our ACCs, the resected group had a significantly longer survival as well.…”
Section: Discussionmentioning
confidence: 56%
“…Many studies in different parts of the world have shown that resection extends the survival of patients with ACC [3,5,8,9,[13][14][15][16][17]. In our ACCs, the resected group had a significantly longer survival as well.…”
Section: Discussionmentioning
confidence: 56%
“…Efor dispnesi ve wheezing olan hastalarda ayırıcı tanıya gidilirken çekilen posteroanterior akciğer grafisinin normal olarak değerlendirilmesi üzerine, hastaların çoğun-luğunda sigara içme öyküsü de olduğu için, genellikle trakea tümörleri yerine astım veya KOAH düşünülmektedir. 3,8 Ancak trakea tümörlerinin çok nadir görülmesi nedeniyle bu semptomlar trakea tü-mörlerini ilk olarak akla getirmezler. Trakea lümeni daralmaya devam ettikçe wheezing yerini stridora bırakır, bu durum ise önemli bir darlığın gösterge-sidir.…”
Section: Discussionunclassified
“…Bunun dışında disfaji, tekrar eden pnömoni atakları ve ses kısıklığı da görülebilir. 1,3,8 Bizim hastamızda da 80 paket/yıl sigara içme öyküsü vardı ve müracaat ettiği ilk sağlık kuruluşunda, daha önce-den KOAH tanısı da olduğu için, mevcut hastalığı-nın bir alevlenmesi olarak değerlendirilmişti.…”
Section: Discussionunclassified
See 2 more Smart Citations